INACCURACIES IN AREA OBJECTS TRANSFERRED FROM THE MAP OF THE RESTORED PROPERTY TO THE CADASTRAL MAP: INACCURACIES IN AREA OBJECTS TRANSFERRED FROM THE MAP OF THE RESTORED PROPERTY TO THE CADASTRAL MAP - Niyazi-Yusuf , Mirem (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The cadastral map and cadastral registers are created under conditions of maximum use of the existing map of the restored property and the current cadastral plans of the settlements. In the practice of the Geodesy, Cartography and Cadastre Agency - in the process of creating a cadastral map and cadastral registers and maintaining the already approved cadastral map and cadastral registers in an up-to-date state, discrepancies are found in the non-urbanized territory, which are transferred to the cadastral map and cadastral registers registers from the restored property map.